ZnO Doped Graphite Nanocomposite via Agathosma Betulina Natural Extract with Improved Bandgap and Electrical Conductivity: Experimental Investigation - (:unkn) unknown (My University, 2021)
This contribution reports for the first time on green synthesized Zinc Oxide graphite doped (ZnO/G) material that was fabricated and exposed to UV lamp irradiation at 250 nm for 4 hrs. The objective is to induce electrical properties by narrowing the bandgap of the as prepared composite. The morphology and the structure of ZnO and ZnO/G were characterized by high resolution transmission electron (HRTEM) and X-ray diffraction (XRD) respectively. The Energy Dispersive spectroscopy (EDS) confirms the purity of ZnO nanoparticles which is substantiated by the XPS spectrum. Diffuse Reflectance spectroscopy (DRS) reveals decrease in bandgap and reflectance of the irradiated composite with (I-V) character curve showing enhanced ZnO/G electrical conductivity.
Keywords: African Research